Shipping pollution emission associated with increased cardiovascular mortality: A time series study in Guangzhou, China. (October 2018) - Lin, Hualiang; Tao, Jun; Qian, Zhengmin (Min); Ruan, Zengliang; Xu, Yanjun; Hang, Jian; Xu, Xiaojun; Liu, Tao; Guo, Yuming; Zeng, Weilin; Xiao, Jianpeng; Guo, Lingchuan; et al.
Abstract: Substantial evidence has linked short-term exposure to ambient fine particulate matter (PM2.5 ) with increased cardiovascular mortality, however, the specific chemical constituent and emission source responsible for this effect remained largely unclear. A time series Poisson model was employed to quantify the association of cardiovascular mortality with two sets of shipping pollution emission: nickel (Ni), vanadium (V) (the indices of shipping emission) and estimated shipping emission using a source apportionment approach in Guangzhou, China in 2014. We observed that Ni, V, and estimated shipping emission in PM2.5 were associated with increased cardiovascular mortality, an inter-quartile range (IQR) increase in lag2 Ni was associated with 4.60% (95% CI: 0.14%, 9.26%) increase in overall cardiovascular mortality, and 13.35% (95% CI: 5.54%, 21.75%) increase in cerebrovascular mortality; each IQR increase of lag1 V was correlated with 6.01% (95% CI: 1.83%, 10.37%) increase in overall cardiovascular mortality, and 11.02% (95% CI: 3.15%, 19.49%) increase in cerebrovascular mortality; and each IQR increase in lag1 shipping emission was associated with 5.55% (95% CI: 0.78%, 10.54%) increase in overall cardiovascular mortality, and 10.39% (95% CI: 1.43%, 20.14%) increase in cerebrovascular mortality. The results remained robust to adjustment for PM2.5 mass and gaseous air pollutants. This study suggests that shipping emission is an important detrimental factor of cardiovascular mortality, and should be emphasized in air pollution control and management in order to protect the public health in Guangzhou, China. Graphical abstract: Highlights: We examine cardiovascular effects of ship emission-related air pollution. Nickel, vanadium and estimated ship emission were used as exposure indicator. Ship emission was associated with increased cardiovascular mortality. Abstract : Shipping emission-associated air pollution was associated with cardiovascular mortality in Guangzhou.